Populasi Mikroorganisme Tanah pada Lahan Jagung setelah Aplikasi Pupuk Poliakrilat - Almi Abdila; Nurjannah Japarang; Nur Agustin; Warida Hafni; Alfiqi Dwiva Annisi; Hilda Karim; Andi Asmawati Azis; Muhammad Junda; Oslan Jumadi (Institut Pertanian Bogor, 2022)
The number and type of microorganisms in the soil indicate soil fertility. The use of fertilizers can affect the growth of microorganisms in the soil. Quantitative tests are conducted to evaluate how fertilizers affect the presence of bacteria, fungi, and algae. The number of bacteria and fungi is calculated using the standard plate count method, while the number of algae is calculated using the most probable number method. The highest number of bacteria found in urea-phosphate-potassium (UPK) applications of zeolite polymers is 50%, which is 3.4 × 106 CFU/mL; the most fungi are found in 25% of applications, which is 2.5 × 104 CFU/mL. In contrast, the highest algae population was in control soils, 2.7 × 104 CFU/mL. However, for treatment, an enormous amount is found in the administration of 50% zeolite polymer UPK as much as 1.4 × 103 CFU/mL, so it can be concluded that the administration of UPK zeolite polymer affects the number of microorganisms on the cornfield. Keywords: soil microorganism, polyacrylate, UPK, zeolite